Formation constants in the ternary systems: Co(II)-L-cysteine - Adenine & Zn(II)-L-cysteine-Adenine - (:unkn) unknown (My University, 2001)
A potentiometric titration technique has been used to determine stability constants for the various complexes of Co(II) and Zn(II) with L-cysteine and from DNA bases i.e. Adenine. Stability constants of ternary systems have been evaluated by the method suggested by Irwing-Rossotti. In addition, the conditional constants were calculated as a function of pH. The maximum values of the conditional formation constants were found to be in accordance with the mixed-ligand complex formation constants at a given pH region. Furthermore, the molar fractions of different species from mixed complexes were calculated by means of formation constants. The values of stability constants of mixed-ligand complexes at 25°C are as follows: log K=9.50 for Co(II)-L-cysteine-Adenine; log K1 = 6.85 and log K2 = 6.00 for Zn(II)-L-cysteine-Adenine2. The ionic strength was kept constant at I = 0.20 with NaClO4.
Keywords: Adenine; Cobalt(II) and zinc(II) complexes; L-cysteine; Mixed complexes; Stability constants